Lymph node dissection for gastric cancer: a critical review - Thales Paulo Batista; Mário Rino Martins (Frontiers Media S.A., 2012)
Gastric cancer is one of the most common neoplasms and an important cause of cancer-related death worldwide. Efforts to reduce its high mortality rates are currently focused on multidisciplinary management. However, surgery remains a cornerstone in the management of patients with resectable disease. There is still some controversy as to the extent of lymph node dissection for potentially curable stomach cancer. Surgeons in eastern countries favor more extensive lymph node dissection, whereas those in the West favor less extensive dissection. Thus, extent of lymph node dissection remains one of the most hotly discussed aspects of gastric surgery, particularly because most stomach cancers are now often comprehensively treated by adding some perioperative chemotherapy or chemo-radiation. We provide a critical review of lymph nodes dissection for gastric cancer with a particular focus on its benefits in a multimodal approach.